2015
DOI: 10.1177/0954410015607892
|View full text |Cite
|
Sign up to set email alerts
|

In-flight performance analysis of a non-cooperative radar-based sense and avoid system

Abstract: This paper discusses the outcome of flight experiments relevant to non-cooperative sense and avoid that were carried out in the framework of a collaboration between the Italian Aerospace Research Center and the University of Naples '‘Federico II’’. Within the project, aimed at full autonomy for medium/large Unmanned Aircraft Systems, an integrated radar/electro-optical system configuration was adopted, and real-time data fusion/automatic decision-making algorithms were developed to estimate intruders’ motion, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…In addition, they do need a demanding computation power for their operation [9,10]. Other sensing technologies like radar have been considered in bigger UAS types [9], but mostly as impulse radar systems with larger size and bigger system mass [11]. Preliminary studies have shown that the choice of a miniaturized continuous wave radar system as a possible detection sensor technology offers a promising approach to meet the requirements [12,13] while using only microcontroller resources to compute detection results.…”
Section: Collision Avoidancementioning
confidence: 99%
See 2 more Smart Citations
“…In addition, they do need a demanding computation power for their operation [9,10]. Other sensing technologies like radar have been considered in bigger UAS types [9], but mostly as impulse radar systems with larger size and bigger system mass [11]. Preliminary studies have shown that the choice of a miniaturized continuous wave radar system as a possible detection sensor technology offers a promising approach to meet the requirements [12,13] while using only microcontroller resources to compute detection results.…”
Section: Collision Avoidancementioning
confidence: 99%
“…Regarding classic impulse radar systems like the type used in [11], the utilized sensor has a smaller detection range (2 nautical miles as described in [11] compared to 900 m) but significant lower electrical power consumption and overall sensor system mass (25 kg sensor mass [11] compared to 164 g per continuous wave radar system, which includes the signal processing and hardware interface units).…”
Section: Characteristics Of the Continuous Wave Radar Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Luongo S [5] improved the 3D analytical algorithm by proposing a cylindrical safety bubble that allows different minimum separations of the vertical and horizontal planes with respect to the nominal trajectory to be achieved. The performances of such system, using active obstacle detection through radar, have been discussed in the paper [6]. Geometric algorithm is intuitive with low computing cost and always provides an optimal solution in 3D environments whether the aircraft cooperates or not.…”
Section: Introductionmentioning
confidence: 99%
“…The strategic level approach refers to proactively planning collision-free flight paths from the current location to the destination based on the perceptual detection of obstacles under the constraints of the minimum safe separation distance. Among them, the performance of systems using radar to actively detect obstacles is discussed in [19]. The collision avoidance algorithm based on geometric relationship has the characteristics of simple and efficient calculation, but most of the collision avoidance systems based on geometric relationship only support the collision avoidance between a pair of UAVs.…”
Section: Introductionmentioning
confidence: 99%